PENGARUH STRUKTUR KEPEMILIKAN, STRUKTUR AKTIVA, LIKUIDITAS, RISIKO BISNIS, KEBIJAKAN DIVIDEN, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA INDUSTRI HOTEL, RESTORAN DAN PARIWISATA - agustinus Kismet Nugroho Jati (STIE Perbanas Surabaya, 2016)
The determination of capital structure policy becomes important in the hotels, restaurants and tourism industry in Indonesia. This industry environment has a fairly high business fluctuations because the product that being offered is a product that requires a large capital. The firms in this industry which in have capital intensive, but also have a quite high business risks. On the other hand, firms also need to take care of the capital structure that will be used. It is the goal of this studies so that it can be the information for the firm to determine the optimal capital structure. The results of this study are simultaneously factors managerial ownership structure, asset structure, liquidity, business risk, dividend policy, the size and profitability of the firm has no significant effect on the capital structure of the firm, while only partially profitability factor that showed a significant negative effect on capital structure. This means there is a tendency of firms in this industry in Indonesia to use funding from internal sources to finance its business expansion.